Agreement between the Swiss Agency for Development and Cooperation (SDC) and BRAC University-Institute of Educational Development (BU-IED) concerning the granting of a contribution to project Institute of Education Development (IED) (2009) - Swiss Agency for Development and Cooperation (SDC); BRAC University-Institute of Educational Development (BU-IED) (SDC and BU-IED, 2013)
Agreement between the Swiss Agency for Development and Cooperation (SOC) Represented by the CoordinatiOn Office in Dhaka, Bangladesh and BRAC University-Institute of Educational Development (BU-IED) House No. 113, Road No.2 Niketon Housing, Gulshan-2, Dhaka-1212, concerning the granting of a contribution to project Institute of Education Development (lED) for the period from 15.04.2009 to 31.12.2010.